A novel high dynamic range 3D measurement method based on adaptive fringe projection technique. (May 2020) - Liu, Yanzhao; Fu, Yanjun; Cai, Xiaoqi; Zhong, Kejun; Guan, Bingliang
Highlights: A novel adaptive projection fringe pattern technique is proposed. The proposed method is capable of measuring the small objects with shiny surface. Fringe pattern with low intensity is projected onto the bright region to avoid the pixel saturation. A new algorithm to generate the adaptive fringe patterns is proposed. Compared with the existing methods, the proposed method needs fewer patterns. Abstract: Fringe projection techniques have been widely used in three-dimensional (3D) small-field measurement; however, measuring the 3D shapes of small objects with high ranges of reflectivity across their surfaces remains challenging because image saturation leads to measurement error. In this study, a novel adaptive fringe projection technique was proposed to address this issue. First, a 255 uniform gray-level pattern was projected onto the surface to mark the saturated region in the captured image. Second, another uniform gray-level pattern with lower intensity was used to calculate the reflectivity across the surface and an appropriate projection gray level in the camera coordinate system was calculated at the pixel level. Third, a set of orthogonal sinusoidal fringe patterns were projected onto the object to establish the spatial relationship between the camera and projection systems, and adaptive fringe patterns were generated in the projection coordinate system. Subsequently, the generated adaptive fringe patterns were used to measure the object. The experimental results demonstrate that the proposed method could retrieve the 3D shapes of small shiny objects with high accuracy and relatively few images.